Ontological foundations of the consumer society - Volarević, Martina (Anthropos (Ljubljana), 2022)
This paper analyses the ontological foundations of the consumer society in Heidegger’s thinking of positionality (Ge-stell), and compares that with Marcuse’s exposition of the phenomenon of late capitalist society. The comparison shows a number of similarities: both attribute a totalitarian character to the mechanism of the consumer society, both believe such a society has a negative effect on man, and both find a solution in artistic experience. The presented analysis remains significant because it touches on contemporary ecological dilemmas.
Keywords: consumer society; filozofija; Heidegger, Martin; kapitalizem; Marcuse, Herbert; ontologija; potrošniška družba; potrošništvo